2012
DOI: 10.1373/clinchem.2011.174359
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 and the Development of Heart Failure after Acute Coronary Syndrome: Pilot Experience from PROVE IT-TIMI 22

Abstract: BACKGROUND Galectin-3 is a β-galactoside–binding lectin that has been implicated in cardiac fibrosis and remodeling, is increased in models of failure-prone hearts, and has prognostic value in patients with heart failure (HF). The relationship between galectin-3 and the development of HF after acute coronary syndrome (ACS) is unknown. METHODS In a nested case-control study among patients with ACS in PROVE IT-TIMI 22, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
3
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 27 publications
4
47
3
3
Order By: Relevance
“…Hence, with the strength of a prospective cohort study design and of a large cohort of consecutively enrolled patients, our data demonstrate that Gal-3 predicts cardiovascular mortality in patients with CAD regardless of the presence or absence of left ventricular systolic dysfunction. This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events.…”
Section: Subgroup Analysescontrasting
confidence: 99%
See 2 more Smart Citations
“…Hence, with the strength of a prospective cohort study design and of a large cohort of consecutively enrolled patients, our data demonstrate that Gal-3 predicts cardiovascular mortality in patients with CAD regardless of the presence or absence of left ventricular systolic dysfunction. This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events.…”
Section: Subgroup Analysescontrasting
confidence: 99%
“…This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events. Another possibility is that adjustment for the Duke CAD Index Score, one of the strongest predictors of cardiovascular events and death in patients with CAD, might have concealed an effect of Gal-3 on these end points in the our study.…”
Section: Subgroup Analysescontrasting
confidence: 99%
See 1 more Smart Citation
“…Three covariates, LVEF < 45%, RVSP and age, were significant, but in a multivariate model, after excluding RVSP, which predicts 33.2% of LAVI variance, none of the dependent variables remained independently significant. Previous clinical findings showed that serum Gal-3 levels are correlated with LAstructural remodeling (9). Atrial size is an important determinant of AF and patients with larger atria have a higher probability for the initiation and maintenance of rotor-driven fibrillatory activity.…”
Section: Discussionmentioning
confidence: 93%
“…Збільшення концентрації креатиніну в плазмі кро-ві на ≥0,5 мг/дл у першу добу госпіталізації підвищує ризик смерті впродовж наступних 12 місяців, а зрос-тання рівня креатиніну в плазмі крові до 1,5-2,4 мг/дл супроводжується збільшенням ризику смерті впро-довж 1-го року після розвитку ГІМ в 2-3 рази [9]. Що стосується галектину-3, у дослідженні PROVE IT-TIMI 22 було показано стійкий зв'язок даного пока-зника з розвитком патологічного ремоделювання міокарда у пацієнтів, які мали гострий коронарний синдром в анамнезі, а також визначено галектин-3 як незалежний маркер прогресування серцевої недо-статності [8]. За даними В.Й.…”
unclassified